Transactional Leadership And Organizational Performance Of Private Universities In Kenya - Kubai, Polycarp Koome; Gachunga, Hazel; Odhiambo, Rhomanus (Machakos University Press, 2021)
Private universities are undergoing through tough times due to reduced number of students, financial crisis, poor academic programs and general management crisis. The manner in which the vice chancellors dispense with their authority has to a great extent affected the performance of lecturers which has great effect to the performance of these universities. Therefore, this study sought to find out the effect of transactional leadership style on the performance of in private universities in Kenya. Descriptive research design was used as a method of study. The study used primary data collected by use of structured questionnaires. Data obtained was cleaned, coded and entries made into Statistical package for social sciences. Descriptive and inferential analysis was conducted for quantitative data. Mean and standard deviations were also used as measures of central tendencies and dispersion respectively. Results were presented in form of tables and charts. The study found that transactional leadership had a significant and positive influence on performance of private universities in Kenya. The study further established that the perceived supervision support had insignificant moderating effect on the relationship between transactional leadership and performance of private universities in Kenya. The study concluded that as a result of transactional leadership, performance of private universities in Kenya was enhanced. The study recommended that the private universities which face performance challenges should uphold transactional leadership as an aspect of integrative leadership so as to steer their performance.
Keywords: Leadership; Transactional Leadership; Integrative Leadership; Private Universities; Chattered Universities